2016
DOI: 10.1016/j.apsusc.2016.02.148
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and oxygen incorporation effect on antimicrobial activity of silver thin films

Abstract: Ag and Ag x O thin films were deposited by non-reactive and reactive pulsed DC magnetron sputtering, respectively, with the final propose of functionalizing the SS316L substrate with antibacterial properties. The coatings were characterized chemically, physically and structurally. The coatings nanostructure was assessed by X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS), while the coatings morphology was determined by scanning electron microscopy (SEM). The XRD and XPS analyses suggested tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 31 publications
3
24
0
Order By: Relevance
“…However, metallic silver which is not oxidized was shown already in 1937 to be devoid of antibacterial activity. 35 This was subsequently confirmed in various other studies, most recently by Rebelo et al 36 In agreement with these findings, we found that silver does not exhibit detectable contact killing over 6 h and only marginal killing (less than 1 log) in 9 h [ Fig. 3(a)].…”
Section: Contact Killing By Silversupporting
confidence: 92%
“…However, metallic silver which is not oxidized was shown already in 1937 to be devoid of antibacterial activity. 35 This was subsequently confirmed in various other studies, most recently by Rebelo et al 36 In agreement with these findings, we found that silver does not exhibit detectable contact killing over 6 h and only marginal killing (less than 1 log) in 9 h [ Fig. 3(a)].…”
Section: Contact Killing By Silversupporting
confidence: 92%
“…increase in crystallinity of the silver oxide thin films due to the increase in the rate of oxygen difusion into the silver oxide thin film deposited at 350W compared to silver oxide thin film deposited at 300W and 250W , resulting in larger grain sizes for silver oxide deposited at 350W [13,[19][20][21][22][23]. This is in agreement with the scanning electron microscopy images, where there are more pronounced micropores on silver oxide films sputtered at higher forward power.…”
Section: Accepted Manuscriptsupporting
confidence: 81%
“…Figure 2 (a and b) shows the Ag 3d and O 1s spectra, with binding energy observed at 368.3ev consistent with Ag sample [19,[27][28][29][30]. The existence of Ag-O bond was also evident in the O 1s spectra, with peak at 531.8 eV [19,[31][32]. The 531.8 eV peak originates from the subsurface formation of oxygen, which is a mixture of oxygen and the hydroxyl group.…”
Section: Xpsmentioning
confidence: 68%
“…The surface-dependent factors like distribution, size, concentration, shape or charge of the antibacterial substance, the porosity and roughness of the coating's matrix as well as the overall micro-and nanostructure of the coating, are known to influence the ion release kinetics [32]. In this regard, a fine particle size and the incorporation of oxygen species can improve the Ag ions dissolution rate [33]. Additionally, nano-structuring the surface is also a valuable method to control antibacterial activity due to the high surface to volume ratio, which increases the surface reactivity [34].…”
Section: Introductionmentioning
confidence: 99%